Analisis Efektivitas Sistem Informasi Akuntansi Dalam Pengelolaan dan Pertanggung Jawaban APBDES Pada Pemerintahan Desa Cinta Makmur Kecamatan Panai Hulu Kabupaten Labuhan Batu - Andri Ariansyah Nasution; Rahmi Syahriza; Nur Fadhilah Ahmad Hasibuan (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Village Government is required to be transparent and informative regarding every realization of APBDes implementation. To provide information and ensure ease of obtaining information, a supporting information system is needed, namely an accounting information system. An accounting information system can be said to be effective depending on the ease of the system and the use of the system by its users. This research has a problem formulation, namely how is the accounting information system in the management and accountability of APBDes in the Cinta Makmur village government, is the accounting information system in the management and accountability of APBDes implemented? by the Cinta Makmur Village government has been running effectively, and what are the obstacles and efforts in the accounting information system in the management and accountability of the APBDes implemented by the Cinta Makmur village government. The approach method used is descriptive qualitative to produce descriptive data in the form of written or spoken words from people and observed behavior. Based on the results of this research, the accounting information system in the Cinta Makmur village government is less effective. So it is recommended to the Cinta Makmur Village Government to provide further training for village officials regarding the preparation of APBDes reports and the implementation of accounting information systems in order to increase the effectiveness of implementing the accounting information system in Cinta Makmur Village.